Estudo do aço como objeto de reforço estrutural em edificações antigas - Izabela Naves Coelho Teobaldo (2004)
This research seeks the construction of an interface between intervention principles over old buildings and steel constructive technology, aiming to approach both areas and the construction of a knowledge about the possibilities and responsibilities involved inworks over this kind of buildings, inclusive the built historical patrimony.In this context, the use of metallic structure as consolidator element or structural reinforcement, is an area in development. The evolution of restoration in Brazil, impelled by the revision of the preservation politics and by new tendencies of the civil construction, demands for studies related to the methodologies and project conceptions, scarce in the practice. With the purpose of diffusing the use of the steel in the consolidation of old buildings, this research, in a first moment, tries to characterize the steel structure in the civil construction and the area of the restoration of the historic buildings through theoretical researches. Then, the subject of the intervention with metallic structures in old buildingsis better detailed and illustrated starting from cases and scientific tudies. Finally, buildings, which have been submitted to some kind of intervention are analyzed to verify if the dialogue between the knowledge about steel structures and intervention principles has occurred.